2005
DOI: 10.1016/j.jvs.2005.04.042
|View full text |Cite
|
Sign up to set email alerts
|

High-energy phosphate metabolism in the calf muscle during moderate isotonic exercise under different degrees of cuff compression: A phosphorus 31 magnetic resonance spectroscopy study

Abstract: Our study shows that the ischemic condition during constant muscle exercise is clearly characterized by PCr and Pi kinetics, as well as by pH changes. The correlation between the degree of blood flow reduction and PCr levels in the exercising muscle groups, which are supplied by the stenosed arteries, is the first essential of using 31P magnetic resonance spectroscopy in the assessment of the effect of arterial stenoses on muscle function in claudicants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 44 publications
2
13
1
Order By: Relevance
“…Furthermore, both the end-exercise PCr level and the end-exercise pH correlated significantly with the RORs. Both parameters reflect the amount of ATP hydrolyzed during muscle contraction and the mismatch of mitochondrial ATP production, which accumulates with increasing impairment of oxygen supply [4,5,13,35]. PCr serves as a Bshuttle^for high-energy phosphates from the mitochondria to the myofibrils, whereby the extent of PCr hydrolysis depends on oxygen uptake, mitochondrial density and function, and work intensity [12,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both the end-exercise PCr level and the end-exercise pH correlated significantly with the RORs. Both parameters reflect the amount of ATP hydrolyzed during muscle contraction and the mismatch of mitochondrial ATP production, which accumulates with increasing impairment of oxygen supply [4,5,13,35]. PCr serves as a Bshuttle^for high-energy phosphates from the mitochondria to the myofibrils, whereby the extent of PCr hydrolysis depends on oxygen uptake, mitochondrial density and function, and work intensity [12,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…11 Previous experimental 31 P MRS studies investigating the impact of cuff stenosis or occlusion on intramuscular high-energy metabolism have shown that phosphocreatine (PCr) hydrolysis becomes progressive under ischemic conditions. 12,13 PCr and its catalysis product creatine serve as shuttle of high-energy phosphates from the mitochondrial to the myofibril site. 14 -16 Under aerobic conditions, the PCr concentration decreases and passes into a steady-state with a typical mono-exponential curve progression at the onset of muscle exercise.…”
mentioning
confidence: 99%
“…3, A and B) or result in a more pronounced decrease in blood pH, indicating that the reduced aerobic energy production was not compensated by a higher anaerobic energy turnover from the glycolytic pathway. However, it cannot be excluded that the reduced O 2 delivery in DB caused a greater degree of muscle creatine phosphate utilization (27) and lactate accumulation (46), and the lower blood flow in DB may have reduced lactate release (56). Nevertheless, the finding of a similar lactate release after 3 and 4 min of exercise when blood flow was not different suggests that the muscle lactate accumulation was not greater in DB compared with CON.…”
Section: R317mentioning
confidence: 96%